2019
DOI: 10.1021/acsmedchemlett.9b00354
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Pyridazinone and Pyrazolo[1,5-a]pyridine Inhibitors of C-Terminal Src Kinase

Abstract: C-terminal Src kinase (CSK) functions as a negative regulator of T cell activation through inhibitory phosphorylation of LCK, so inhibitors of CSK are of interest as potential immuno-oncology agents. Screening of an internal kinase inhibitor collection identified pyridazinone lead 1, and a series of modifications led to optimized compound 13. Compound 13 showed potent activity in biochemical and cellular assays in vitro and demonstrated the ability to increase T cell proliferation induced by T cell receptor si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Pyrazolo­[1,5- a ]­pyridines are prevalent in a wide array of biologically active compounds and marketed drug molecules . Given the salient biological profiles of pyrazolo­[1,5- a ]­pyridine-based molecules, it is no surprise that a handful of powerful approaches have been developed to construct this skeleton .…”
mentioning
confidence: 99%
“…Pyrazolo­[1,5- a ]­pyridines are prevalent in a wide array of biologically active compounds and marketed drug molecules . Given the salient biological profiles of pyrazolo­[1,5- a ]­pyridine-based molecules, it is no surprise that a handful of powerful approaches have been developed to construct this skeleton .…”
mentioning
confidence: 99%
“…CSK is a no-receptor tyrosine kinase that is considered to be an indispensable negative regulator of Src family kinases (SFKs) [29]. It consists of three Src homologous domains: N-terminal Src homologous 3 (SH3), SH2, and C-terminal kinase [30]. Extensive evidence has shown that CSK plays an important role in the signal transduction pathways of immune receptors, including promoting the innate immune response and inhibiting T cell or mast cell activation [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies: anti-PEAK2 and anti-PEAK2 pY413 were described in [ 11 ]; anti-ABL was described in [ 27 ]; anti-ABL pY412, anti-ERK1/2, anti-ERK1/2 pT202/Y204, anti-AKT, anti-AKT pS473, anti-pTyr clone pY1000 Sepharose bead conjugated (PTM Scan, Cell Signalling Technology, Danvers, MA, USA); anti-Hes1, anti-Actin, anti-AMPK, and anti-AMPK pT172; anti-Myc tag (9B11) were from Cell Signalling Technology; antitubulin (gift from N. Morin, CRBM, Montpellier, France); anti-ATOH1 (EPR6419, Abcam, Cambridge, UK); anti-pY418 SRC (Biosource, Camarillo, California, US), anti-pTyr 4G10 (gift from P. Mangeat, CRBM, Montpellier, France); anti-cst1 (that recognizes SRC, FYN and YES) was described in [ 28 ]; antirabbit IgG-HRP and antimouse IgG-HRP (GE Healthcare, Chicago, IL, USA). Kinase inhibitors: Imatinib, dasatinib, bosutinib, lapatinib, PP2 were from Sigma-Aldrich, (St. Louis, MI, USA); nilotinib and CSKi (compound 13 ) [ 29 ] was a gift from Novartis (Basel, Switzerland) and Bristol-Myers Squibb Company (New York, NY, USA), respectively. Fibronectin human plasma (F0895) and rat tail collagen I (#C3867) were from Sigma.…”
Section: Materiel and Methodsmentioning
confidence: 99%